PENGARUH PERSEPSI DAN PENGETAHUAN AKUNTANSI PELAKU UMKM JAJANAN KHAS TRENGGALEK TERHADAP PENGGUNAAN INFORMASI AKUNTANSI - Alisa, Alisa; Rachmanasuha, Salisa (PT Naureen Digital Education, 2025)
Micro, Small and Medium Enterprises (MSMEs) are a sector that is the main pillar of the Indonesian economy. MSMEs not only act as the main driver of economic growth, but also have a significant contribution to employment. According to Law Number 20 of 2008, MSMEs are productive economic businesses owned by individuals or individual business entities, which are not subsidiaries or branches of large companies. The purpose of this study is to analyze percepcion and accounting knowledge of Micro, Small, and Medium Enterprises (MSME) actors specializing in Trenggalek’s traditional snacks on the use of accounting information. This research employs a quantitative approach with a causal-comparative design. The sample consists of 35 MSME owners selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression tests. The results show that accounting knowledge has a significant influence on the use of accounting information, while accounting perception individually does not have a significant effect. However, simultaneously, accounting perception and knowledge influence the use of accounting information by 83.9%. This highlights the importance of improving accounting literacy among MSME actors to support better financial management and decision-making processes.